A monitor unit Calculator Program Using Digital Simulator Images - Anusornthanawat, Kiattisak; Wanwilairat, Somsak; Tharavichitkul, Ekkasit; Chaiwiang, Thanit; Wanwilairat, Sumbhat (Naresuan University Journal: Science and Technology (NUJST); Vol 26 No 3 (2018): July-September 2018, 2018)
Calculation of the monitor unit is the first important step in radiation therapy. If the calculation of the monitor unit has deviations, it will adversely affect the treatment. The irradiation area, the main factor affecting the calculation of the monitor unit, and if there is any deviation from that area, the monitor unit calculation will have an error too. The objective of this study was to develop a program to calculate the monitor unit from the digital simulator images. Test cases of the radiation area were selected from the IAEA TECDOC 1540 guidelines, and the length of the equivalent radiation areas were calculated in two ways: “Eqs and SQRT”, using the JAVA language to determine the radiation field parameters, and “TMR and S c,p ”, calculated from beam data to and calculated the monitor unit by using the approximation method, which was programmed with the Visual Fox Pro language. The results were verified against the IAEA TECDOC 1540 guidelines.      The results, the test case area that calculating on central axis (square and rectangular), the mean difference percent in radiation dose of the equivalent radiation areas with Eqs length passes + 2% tolerance. The mean difference percent in radiation dose of the equivalence areas with  SQRT length were not pass + 2% tolerance.The results of the covered test area and off axis, the lengths of Eqs and SQRT radiation areas were not pass + 3% tolerance.      To conclude, the monitor unit calculator program could be used the digital simulator images for calculation the length equivalent radiation area (Eqs). In addition, this program could calculate monitor unit in the central axis accurately. Keywords: monitor unit calculator program, approximation method, irradiation area image
Keywords: Monitor Unit Calculation Program, approximation method, irradiation area image